2020
DOI: 10.1038/s41598-020-72769-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chloroplast genomes in Vasconcellea pubescens A.DC. and Carica papaya L.

Abstract: The chloroplast genome is an integral part of plant genomes in a species along with nuclear and mitochondrial genomes, contributing to adaptation, diversification, and evolution of plant lineages. In the family Caricaceae, only the Carica papaya chloroplast genome and its nuclear and mitochondrial genomes were sequenced, and no chloroplast genome-wide comparison across genera was conducted. Here, we sequenced and assembled the chloroplast genome of Vasconcellea pubescens A.DC. using Oxford Nanopore Technology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
2
6
0
1
Order By: Relevance
“…Further, the cp genome was compared with 1). The size range of S. persica cp genome is found in the same range as the sizes of the previously reported cp genomes of A. tetracantha (153,415 bp) and other related species [29,[34][35][36]. Like typical angiosperms cp genomes (20 ± 28 kb), these species' IRs length ranges from 25 to 26 kb in length [34,37].…”
Section: Discussionsupporting
confidence: 77%
“…Further, the cp genome was compared with 1). The size range of S. persica cp genome is found in the same range as the sizes of the previously reported cp genomes of A. tetracantha (153,415 bp) and other related species [29,[34][35][36]. Like typical angiosperms cp genomes (20 ± 28 kb), these species' IRs length ranges from 25 to 26 kb in length [34,37].…”
Section: Discussionsupporting
confidence: 77%
“…Herein, four Cuscuta species (C. epithymum, C. europaea, C. approximata and C. pedicellata) lacked an IR region (Table 1). The loss of IR is common in the chloroplast genomes of higher plants [37]. These results further con rmed the structural plasticity of the chloroplast.…”
Section: Variation In Chloroplast Gene Structuresupporting
confidence: 65%
“…), and more commonly in Angiosperms, with 58 species across 16 other orders showing similar patterns [22]. Recent studies have also revealed the presence of two cp haplotypes in other orders, such as Asparagales ( Ophrys apifera orchid, [72]), Brassicales ( Carica papaya , Vasconcellea pubescens , [73]), Solanales ( Solanum tuberosum , [74]), and even in a new order, Laurales (Avocado Persea americana , [75]). Furthermore, Wanichthanarak et al .…”
Section: Discussionmentioning
confidence: 99%